1982
DOI: 10.1177/00220345820610021401
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Invasion of Pulpal Dentin Wall in vitro

Abstract: Instrumented root canals of extracted human teeth were inoculated with known pulpal bacterial isolates. The inoculated teeth were immersed in the appropriate culture media and incubated at 37 degrees C for varying periods. Streptococci multiplied in the root canals and invaded the radicular dentinal tubules. The extent of bacterial invasion was time-dependent. This experimental model of bacterial invasion was time-dependent. This experimental model may be useful in investigating the effect of intra-canal medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
1
8

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 3 publications
1
87
1
8
Order By: Relevance
“…By contrast to results obtained with gram-positive bacteria, monocultures of gram-negative anaerobic bacteria do not invade dentinal tubules (1,37). This has led to the notion that dentinal tubules may in some way be selective for streptococci and other facultatively anaerobic bacteria.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…By contrast to results obtained with gram-positive bacteria, monocultures of gram-negative anaerobic bacteria do not invade dentinal tubules (1,37). This has led to the notion that dentinal tubules may in some way be selective for streptococci and other facultatively anaerobic bacteria.…”
mentioning
confidence: 80%
“…Previous light microscopy studies have demonstrated that several gram-negative anaerobic bacterial species, such as Prevotella melananogenica (1) and Prevotella intermedia (37), were unable to invade dentin. On the other hand, it has been reported that Porphyromonas endodontalis BN11a-f and P. gingivalis ATCC 33277 in monoculture were able to invade bovine dentinal tubules, although very few tubules were infected (40).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of follow-up studies on endodontic therapy were reported overall success rate of 85% to 90%, the main cause of root canal therapy failure being persistent microorganisms [11,12]. Enterococcus faecalis is one of the most resistant microorganisms found in case of failed root canal therapy [13][14][15]. It is difficult to remove the smear layer, creating condition for the formation of E. faecalis biofilm, in periapical region by using current routine endodontic procedures that depend on chemo-mechanical debridement.…”
Section: Discussionmentioning
confidence: 99%
“…Not all bacteria can be removed, and pulp tissue remnants and bacteria can invade the dentin even if the root canal is prepared with the utmost caution. One report suggested that no cleaning effect is exerted on the root canal wall because it is protected by a smear layer 1) . Root canal therapy is thus dependent on the pharmacological effects of intracanal medications in addition to adequate canal preparation.…”
Section: Introductionmentioning
confidence: 99%